Designing organotrialkoxysilane-functionalized microscale enzyme carrier: Spherical polymersomes with tunable catalytic potential - Pandey P.C.; Pandey A.K.; Narayan R.J. (My University, 2025)
This manuscript describes fabrication of a cross-linked and nanoengineered three-dimensional matrix of polymersomes for encapsulation of macromolecular cargo such as enzymes. Our approach involves the integration of glucose oxidase (GOx) enzyme into networks of a polysaccharide-silica matrix. Direct chemical cross-linking occurs between the residual groups of alginate polymer and the alkoxysilane moieties in a palladium nanoparticle dispersion; a transformation in the chemical configuration of the alginate hydrogel along with precise control over the pore size distribution facilitate immobilization of enzyme. The activity of the polymersomes was evaluated by enzymatic oxidation of the glucose substrate in phosphate buffer through loading different concentrations of GOx. In situ generated H2O2 was decomposed by the as-synthesized Prussian blue nanoparticles, which serve as an excellent peroxidase mimetic. The functional enzyme polymersome system was utilized for in vitro detection of blood glucose values. Graphic abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to The Materials Research Society.